Atomic Force Microscopy for Collagen-Based Nanobiomaterials. (15th February 2017) - Stylianou, Andreas
Abstract : Novel nanobiomaterials are increasingly gaining ground in bioengineering research. Among the numerous biomaterials, collagen-nanobiomaterials, such as collagen thin films, are of great interest since they present a wide range of applications in the fields of biomaterials, tissue engineering, and biomedicine. Collagen type I is the most abundant protein within extracellular matrix and, due to its unique characteristics, is widely used as biomaterial. A thorough characterization of the structure and properties of nanomaterials can be achieved by Atomic Force Microscopy (AFM). AFM is a very powerful tool which can be used to obtain qualitative or quantitative information without destroying the collagen fibrillar structure. This mini review covers issues related to the use of AFM for studying the structure and mechanical properties of collagen-based nanobiomaterials, collagen-substrate interactions during the formation of collagen thin films, collagen-cells interactions, and the collagen-optical radiation interactions.